“I’ll Wrap the F*** Canadian Flag Around Me”: A Nationalist Response to Plant Shutdowns, 1969-1984 - High, Steven (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 2001)
AbstractDuring the economic slowdown of the 1970s and early 1980s, Ontario trade unionists literally wrapped themselves in the maple leaf flag in order to defy foreign-owned companies that wished to abandon workers with little or no compensation on plant closings. The workers' efforts were not in vain, as the flag's teflon-coating at least partially prevented economic displacement from sticking. Indeed, the Ontario workers' strong national identification with Canada proved to be effective in pushing reluctant politicians to regulate plant shutdowns, thereby mitigating some of the worst effects of job loss.